Research on copper-67 separation obtained by photo-nuclear from zinc of natural composition - Azarov, O.I.; Bocharov, V.O.; Stoyanov, O.F. (Вопросы атомной науки и техники, 2020)
In the world, it is planned to produce promising for the manufacture of radiopharmaceuticals of radioisotope copper-67 by the reaction of its production from zinc-68 under the influence of γ-radiation on an electron accelerator. The next major issue is the separation of copper and zinc. Extraction, ion exchange and thermal distillation of zinc have already been studied in detail. Co-precipitation of copper with low zinc and thermal distillation of organic compounds of metals is promising. У світі планується виробляти перспективний для виготовлення радіофармпрепаратів радіоізотоп міді-67 по реакції ії одержання з цинку-68 під впливом γ-випромінювання на прискорювачі електронів. Наступною за значенням проблемою є розділення міді і цинку. Вже докладно досліджені екстракція, іонний обмін та термічна відгонка цинку. Перспективним є співосадження міді з малою кількістю цинку і термічна відгонка органічних сполук металів. В мире планируется производить перспективный для приготовления радиофармпрепаратов радиоизотоп меди-67 по реакции еe получения из цинка-68 под действием γ-излучения на ускорителе электронов. Следующей по значению проблемой является разделение меди и цинка. Уже подробно исследованы экстракция, ионный обмен и термическая отгонка цинка. Перспективным является соосаждение меди с малым количеством цинка и термическая отгонка органических соединений металлов.